A Distributed Reactive Synchronous Programming Language - Librelotto, Giovani Rubert; Gassen, Jonas Bulegon; Turchetti, Rogério Corrêa; Toscani, Simão Sirineo (INFOCOMP Journal of Computer Science, 2008)
RS is a reactive synchronous programming language suited to the implementation of the control part of reactive systems. The RS source programs are compiled to finite automata, which are very fast at execution time. This paper describes: (1) the distribution of the RS language, (2) the design of an MDX kernel that implements the communication facilities for the distributed automata, and (3) the implementation of the resulting distributed model using the C language.